On the uniform convergence of wavelet expansions of random processes from Orlicz spaces of random variables. II - Kozachenko, Yu. V.; Perestyuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish conditions under which wavelet expansions of random processes from Orlicz spaces of random variables converge uniformly with probability one on a bounded interval.